Preliminary Results of the First 50 Patients Undergoing Sclerotherapy for II-Degree Hemorrhoidal Disease Using an Automated Device - Goglia, Marta; Nigro, Casimiro; Aurello, Paolo; Diaco, Elia; Trompetto, Mario; Gallo, Gaetano (Frontiers in Surgery, 2022)
Background Sclerotherapy is defined as the injection of sclerosant materials causing fibrosis and scarring of the surrounding tissue. It is today employed for the treatment of I-III degree hemorrhoidal disease (HD). The aim of this study is to investigate the use of a new automated device for the injection of a polidocanol 3% foam. Methods This is an observational study including 50 patients who underwent sclerotherapy procedure with 3% polidocanol foam for II-degree HD according to Goligher classification. Patients were evaluated through validated scores [Giamundo score, Hemorrhoidal Disease Symptom Score (HDSS), Short Health Scale (SHS-HD) and Vaizey score]. Follow up was conducted until 3 months from the procedure. Results Complete resolution of bleeding was achieved in 72% and 78% of patients, respectively, at one week and after three months from the procedure. Fourty eight percent of patients were symptom free after the last follow-up visit (HDSS = 0). No major surgical complications were reported. Three patients out of 36 successfully treated, recurred, and needed a second sclerotherapy injection which was successful in 2 of them. Conclusions These preliminary results of 3% polidocanol foam injection on 50 patients suggest the efficacy and reproducibility of the technique with this new device in the short-term follow-up.